Comparative proteomic analysis between tumor tissues and intratumoral exosomes from lung adenocarcinoma patients identifies PAFAH1B3 as an exosomal protein key for initiating metastasis in lung adenocarcinoma - Congcong Wang; Ling Xiao; Ling Gao; Jia Wu; Siliang Wang; Miao-Miao Zheng; Chen-Tai Qin; Xian-ge Huang; Lei Zhou; Wei-jie Xu; He-gen Li; Wen-Lian Chen; et al. (Heliyon)
Mounting evidence strongly indicates that exosomes are pivotal in the advancement of cancer, yet the overarching profile of exosomal proteins and their contribution to lung adenocarcinoma (LUAD) progression remain underexplored. In our investigation, we isolated exosomes from treatment-naive LUAD (n = 20) and paired normal adjacent tissues (NATs), and conducted integrated proteomic on the acquired exosomes and source tissues to ascertain origin characteristics and potential therapeutic targets of the exosomal proteins in LUAD. The omics data revealed the overall landscape of exosomal proteins from tissues in LUAD, underscoring the profound linkage between exosomal proteins and tumor metastasis. Integrated analysis indicated a significant overlap in protein species, demonstrating high concordance between exosomal proteins and those in their originating tissues. However, only a small subset showed significant positive correlation in protein abundance between exosomes and their source tissues. Notably, we pinpointed five proteins (DDX18, DNAJA3, PAFAH1B3, BAG6, and CAD). Significantly, platelet activating factor acetylhydrolase 1b catalytic subunit 3 (PAFAH1B3), an essential serine hydrolase within cellular metabolic processes, stood out as the singular protein closely associated with disease-free survival (DFS) of patients. Cell invasion and migration assays further substantiated that PAFAH1B3 promoted metastasis of LUAD via the exosomal release pathway. Furthermore, analysis of public databases validated elevated PAFAH1B3 expression in LUAD and linked it to poor patient survival outcomes. Overall, our research positioned PAFAH1B3 as a promising candidate for prognostic marker and potential therapeutic target in lung cancer treatment.